Study of profile of polymorphous light eruption at a tertiary referral center - Kulkarni, Amruta A.; Phulari, Yoganand J. (International Journal of Research in Dermatology, 2018)
Background: Polymorphous light eruption (PMLE) is the most common endogenous photodermatosis.But only few studies are available from India regarding this photodermatosis. It is common in women, often worse in spring. The lesions are usually monomorphous in an individual patient but polymorphic in different patients. Methods: The study was conducted between October 2010 and March 2012. 78 patients with clinical diagnosis of PMLE, who attended Dermatology OPD at Dr. D. Y. Patil Hospital and Research Institute, Kolhapur were included in present study. Detailed history, clinical examination and relevant investigations were done. The collected data were tabulated and analyzed. Results: The age group of the patients ranged from 3 years to 58 years. Maximum number of patients were seen in the age group of 21-30 years. The female to male ratio was found to be 1.78:1.Onset of PMLE lesions was maximum in the month of March. Majority of patients were housewives. Itching was the most common symptom. In 32.05% of patients, lesions developed within 30 minutes of sun exposure. Family history of PMLE was present in 6 (7.69%) cases. Conclusions: PMLE was found most commonly in second and third decades of life since people in this age group are more exposed to sun, more in women probably because of hormonal differences.The maximum number of cases was noted in the month of March when the sun exposure is high. The maximum cases in housewives, as they have short intermittent sun exposure and absence of hardening phenomenon. Higher incidence was noted with cotton clothing as it has lower UV protection. Most of the patients developed lesions within 30 minutes of sun exposure. History of recurrence of PMLE was noted in 30 patients. Only 6 patients gave family history of PMLE because of milder nature of the disease along with difference in clothing and working environment.